FORMAÇÃO DE PROFESSORES: UM OLHAR PARA A SUBJETIVIDADE DOCENTE - MUNARI, KEITI DE BARROS (2016)
The teaching profession has been gradually marked by political reforms in an attempt to meet the emergency needs that the socioeconomic and cultural system requires. So in every attempt to adapt teaching to meet the demands of the new capitalism, new means are created to achieve standard or hegemonic models in teacher training. This trend, in a way, as observed by Sousa and Villas Boas (2011), has created a moment of discomfort in the area; a time of uncertainty that generates "generic political responses" without contextualization of the teaching profession in their practices. In this research, we try to deepen themes that articulate factors of academic disciplinary training with teacher professionalization. We focus on the specific characteristics of the profession through aspects of social subjectivity that are transmitted to teaching. We believe we can well understand why, although inserted in an environment of bad feelings towards the career of teaching, we still have teachers who remain in the profession showing satisfaction with their activities - although this might seem to be a paradox. We study whether aspects of social subjectivity promote an intersection of theory with practice and, above all, the academic training that perpetuates the theoretical and disciplinary knowledge with the knowledge built from the context of belonging, held by subjects in a profession which we believe to be relational. In order to do so, we attempt to trace the profile of the participant subjects in this study from the specific characteristics of the behavior of these professionals in the relationship which is maintained with others in the classroom, of what characterizes this group, their expectations regarding teaching and some of the main reasons that lead them to remain in their profession. Based on these observations, we address our theoretical framework based on the concept of Teaching Subjectivity, a topic that has brought some modest contributions to education studies. Our field research was supported by the methodological approach through the measuring instrument known as Q-sort technique - a tool used for qualitative analyzes that focuses issues of subjectivity. The study subjects were teachers of the first grades of public elementary schools, who work in Nazaré, a city in São Paulo state. For the study of the results of the research, we took contributions from participant observation into account.